A Case Study on Business Strategy of Lion Sankyu Tekko Sdn. Bhd - Mazlan, Mufadzir Huzaireen (1998)
Lion Sankyu Tekko Sdn Bhd (LST) is a subsidiary of The Lion Group was set up back in 1994. The merge among the pioneer in pre - engineered steel building systems in Malaysia , PMB Building System Sdn Bhd and Japan's Sankyu Inc. and Tokyo Boeki Ltd., the former being one of the subsidiaries of Nippon Steel Corp. (Japan's largest steel manufactures), was to draw the decades of expertise and experience in the steel fabrication and manufacturing industry to ensure the highest quality structural steel building products at competitive price for the ASEAN region and beyond. LST, during the two financial years in operation has sustained operating loses totaling RM 668 thousand but subsequently improved over the preceding years. However, the economy that grew steadily over the last nine years is now applying its brakes and as a result of financial crisis currently, LST had made a loss of RM 55 thousand in Financial Statement for the period ended 31st May 98. This scenario has urged LST to formulated alternative strategies in order to be better. SWOT and SPACE MATRIX analysis had been used in this case to analyze the company position. Various strategies alternative had been identified and by knowing the company's distinctive competence, perhaps will provide the company guidance during unfavorable situation.